Cognitive behavioral therapy: A comprehensive and culturally attuned analysis of core mechanisms, therapeutic alliance, and self-regulatory outcomes - Danish, Fajer (Global Journal of Social Sciences Studies, 2025)
Cognitive Behavioral Therapy (CBT) stands out as a leading evidence-based psychotherapy, characterized by structured, goal-directed strategies aimed at addressing maladaptive thought patterns and behaviors. This paper provides an integrative reevaluation of CBT, spotlighting key pillars, cognitive restructuring, behavioral activation, therapist-client alliance, and self-regulation, within the context of ongoing developments between 2020 and 2025. A structured narrative review, encompassing meta-analyses and emerging clinical frameworks, was conducted to illustrate how CBT facilitates sustainable psychological change. The review methodically assessed how CBT’s systematic interventions, collaborative engagement, and expanded skill application of cognitive behavioral skills contribute to effective treatment outcomes across various populations in both traditional and modern clinical settings. The findings emphasize CBT’s success in targeting dysfunctional cognitions and maladaptive actions, supported by a strong therapeutic bond and a focus on self-management. In addition, digital delivery models and culturally responsive adaptations are highlighted as cutting-edge strategies that significantly elevate CBT’s global accessibility and clinical relevance among youth, adults, and elderly populations. CBT remains a central yet continuously evolving modality, delivering symptom relief and promoting long-term psychological resilience. Future investigations should explore therapist competencies, deepen cultural sensitivity, and refine digital implementation to ensure CBT aligns with the diverse needs of clinical populations worldwide.